1999
DOI: 10.21273/hortsci.34.4.641
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Fertilization to Maximize Carrot Yield and Quality on a Sandy Soil

Abstract: Nitrogen is required for successful carrot production on sandy soils of the southeastern United States, yet carrot growers often apply N in amounts exceeding university recommendations. Excessive fertilization is practiced to compensate for losses of N from leaching and because some growers believe that high rates of fertilization improve vegetable quality. Carrots (Daucus carota L.) were grown in three plantings during Winter 1994–95 in Gainesville… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
34
5
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(52 citation statements)
references
References 19 publications
11
34
5
2
Order By: Relevance
“…When N is the limiting nutrient, increasing the N supply usually enhances top (shoot) growth more than root growth, resulting in a lower root/shoot ratio (Marshner 1998;Hochmuth, Brecht, and Bassett 1999;Warncke 1996). In our study, tops continued to accumulate N up to the 180 kg ha −1 rate (treatment 4) at most locations; nevertheless it was not reflected in the yield (Table 4).…”
Section: Downloaded By [Duke Universitymentioning
confidence: 54%
See 1 more Smart Citation
“…When N is the limiting nutrient, increasing the N supply usually enhances top (shoot) growth more than root growth, resulting in a lower root/shoot ratio (Marshner 1998;Hochmuth, Brecht, and Bassett 1999;Warncke 1996). In our study, tops continued to accumulate N up to the 180 kg ha −1 rate (treatment 4) at most locations; nevertheless it was not reflected in the yield (Table 4).…”
Section: Downloaded By [Duke Universitymentioning
confidence: 54%
“…Temperatures ranging from 16 to Nitrogen Timing for Carrot Top and Root Quality 2861 21 • C promote greater sugar accumulation in the roots (Epps 1970;Fritz et al 1998;Golz and Aakre 1993;Mills 2001;Zandstra et al 1986). Loose, deep, and well-drained coarse mineral or organic soils are favorable for growing straight carrot roots, whereas heavy, stony, or compacted soils obstruct root growth, causing forked and misshapen roots (Epps 1970;Fritz et al 1998;Golz and Aakre 1993;Hanlon, Hochmuth, and Campbell 2000;Hochmuth, Brecht, and Bassett 1999;McGiffen et al 1997;Michigan Department of Agriculture 2002;Mills 2001;Zandstra et al 1986). In Michigan, carrots are grown both in deep, well-drained muck with a pH range of 5.5 to 6.2 and in sandy mineral soils with a pH range of 6.2 to 6.8 (Bronick et al 1999;Zandstra et al 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Applied N at the highest rate generally resulted in higher carotenoids in apples (Reay et al, 1998), carrot (Hochmuth, Brecht, & Bassett, 1999), kale (Kopsell, Kopsell, & Curran-Celentaro, 2007), while mid-range applications were most effective in tomatoes (Dorais, 2007;Simonne, Fuzere, Simonne, Hochmuth, & Marshall, 2007), lettuce (CoriaCayupan et al, 2009) and watercress (Kopsell, Barickman, Sams, & McElroy, 2007) (Table 1). A decrease in NO À 3 from 12 to 4 mM/plant resulted in a slight reduction in tomato yield (7.5%), and an increase in fruit eating quality as determined by lower fruit acidity and higher soluble sugars (Be'nard et al, 2009) Bryant et al, 1983).…”
Section: Carotenoidsmentioning
confidence: 99%
“…bCarotene content is reported to increase during storage (Brown, 1949;Clydesdale et al, 1991;Lee, 1986;Rygg, 1949), and some of the samples obtained in February for this study were storage samples. Hochmuth et al (1999) reported that b-carotene concentrations are influenced by nitrogenous fertilizers. In the Mie prefecture, larger amounts of fertilizer are recommended for use in the summer (25 kg/km 2 ) than in the winter (20 kg/km 2 ).…”
Section: Carotene Contentmentioning
confidence: 99%